2021
DOI: 10.30692/sisad.925155
|View full text |Cite
|
Sign up to set email alerts
|

Determining The Factors Affecting The Consumers Use/Not Use Mobile Order Applications

Abstract: Öz:Mobil perakendeciliğin e-ticaretteki pazar payı artmakta, literatürde ise bu kanalın etkinliğinin artmasında kritik öneme sahip olan mobil sipariş uygulamalarına odaklanan çalışma sayısının sınırlı olduğu gözlemlenmektedir. Çalışmanın amacı, tüketicilerin bu mobil uygulamaları kullanımlarını etkileyen faktörlerin ortaya konulmasıdır. Bu amaç doğrultusunda mobil sipariş uygulamasını kullananlar ve kullanmayanlar tüketiciler karşılaştırılmıştır. Ölçek soruları yerel pazarda satış kanalı olarak sadece mobil uy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 78 publications
0
0
0
Order By: Relevance
“…The studies on technology acceptance and use have revealed that the target groups of the studies conducted in Turkey are comprised of a wide variety of audiences including school administrators (Yahşi & Hopcan, 2021), teachers (Duyku 2021Ömrüuzun, 2019), high school students (Diri, & Açıkgül, 2021), banking (Gursel, & Yanartas, 2021), women entrepreneurs (Özsungur, 2019), and consumers (Gündoğan, & Kazançoğlu, 2021;Belge, & Mutlu, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The studies on technology acceptance and use have revealed that the target groups of the studies conducted in Turkey are comprised of a wide variety of audiences including school administrators (Yahşi & Hopcan, 2021), teachers (Duyku 2021Ömrüuzun, 2019), high school students (Diri, & Açıkgül, 2021), banking (Gursel, & Yanartas, 2021), women entrepreneurs (Özsungur, 2019), and consumers (Gündoğan, & Kazançoğlu, 2021;Belge, & Mutlu, 2020).…”
Section: Introductionmentioning
confidence: 99%